“THANK YOU, IT REALLY MAKES MY DAY”: COMPLIMENT RESPONSES REVISITED - Shofiyyahtuz' Zahro; Emy Sudarwati (Universitas Islam Sumatera Utara (UISU), 2021)
Complimenting is a typical speaking act and the method in which it is responded to can vary based on the culture of the speakers as well as the influence of other circumstances. The purpose of this study was to provide a more in-depth knowledge of compliment response research based on how it is used by university students learning EFL in everyday life. Furthermore, this study also aims at finding out if exposure to another culture affects university students learning English as a second language while responding to compliments. The data were garnered using data elicitation method by complimenting the participants’ look, possession, character, or aptitude. The finding found that the participants used ten types of responses; listed from the most frequently used type of compliment responses to the least used type of compliment responses: Comment Acceptance (8), Appreciation Token (2), Comment History (2), Question (2), Praise Upgrade (1), Reassignment (1), Return (1), Scale Down (1), Disagreement (1), and Qualification (1). According to the data, the majority of students in an international English literature class at Brawijaya University are likely to accept the compliments. Students tend to take compliments by thanking them and then making related comments. English-speaking countries consider a simple